Teaching young children social studies - Mindes, Gayle (Lanham : Rowman & Littlefirld, 2006)
By linking theory to practice with an emphasis on national and state standards, Head Start Performance Standards, No Child Left Behind, and IDEA, the authors coherently combine principles of child development and social studies content to create a solid program for preschool through grade three.
Includes index.
Keywords: Social sciences -- Study and teaching (Early childhood) -- United States